Pendampingan Pemanfaatan Google Classroom dalam Pembelajaran Online untuk Guru MI Al Ma’arif 05 Banjararum - Wulandari, Tri Candra; Abidin, Zaenal (Universitas Nusantara PGRI Kediri, 2022)
The Covid-19 pandemic that hit the world and Indonesia also has an impact on learning activities in madrassas. Mastery of information technology is currently eeded by teachers, significant changes in learning must be balanced with an increase in teacher skills in making learning innovations that are appropriate to the situation and conditions. Teachers have difficulty in delivering material and limited memory for storing documents of student work. The problems faced by the teachers at MI Al Ma'arif 05 Banjararum can be overcome, one of which is by using the Google Classroom application. This activity is carried out through workshops and mentoring. The workshop was attended by 16 participants consisting of 15 teachers and 1 madrasah principal. At the time of delivering material about Google Classroom, the teacher immediately practiced installing Google Classroom either via Smartphone or laptop. The existence of this activity, the teacher gets a solution in implementing online learning. This activity also had a positive impact on MI Al Ma'arif 05 Banjararum teachers in an effort to improve the quality of learning, especially in online learning.